2015
DOI: 10.1007/s10854-015-3723-7
|View full text |Cite
|
Sign up to set email alerts
|

A new microwave dielectric material ZnZr0.8Sn0.2Nb2O8

Abstract: A novel low-loss microwave dielectric material ZnZr 0.8 Sn 0.2 Nb 2 O 8 was reported for the first time. The samples were prepared by the conventional solid-state reaction route and sintered in the temperature range of 1225-1325°C for 6 h. Single phase ZnZr 0.8 Sn 0.2 Nb 2 O 8 was obtained and it showed monoclinic structure. The microstructure and microwave dielectric properties were investigated systematically. The variation trend of dielectric constant (e r ) was in accordance with variation trend of relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…As shown above, the theory of bond valence and packing fraction is suitable for the discussion of dielectric properties of (La, Sm)NbO 4 system. To further test the applicability of this theory, we reviewed the literatures about the microwave ceramics with similar structure, such as Zn 0.5 Mg 0.5 ZrNb 2 O 8, Zn 0.95 M 0.05 ZrNb 2 O 8 (M=Ni, Mg, Co and Mn), ZnZr 0.8 Sn 0.2 Nb 2 O 8, Zn 0.9 Ti 0.8− x Sn x Nb 2.2 O 8 ( x =0‐0.15), ZnZrNbTaO 8, ZnTiNbTaO 8, (Mg 0.97 M 0.03 ) TiO 3 (M=Ni, Zn, Co and Mn), Ba(Co 0.2 Mg 0.8 ) 2 (VO 4 ) 2, Zn 3 Nb 2 O 8. These representative materials are pure and densified in the references.…”
Section: Resultsmentioning
confidence: 99%
“…As shown above, the theory of bond valence and packing fraction is suitable for the discussion of dielectric properties of (La, Sm)NbO 4 system. To further test the applicability of this theory, we reviewed the literatures about the microwave ceramics with similar structure, such as Zn 0.5 Mg 0.5 ZrNb 2 O 8, Zn 0.95 M 0.05 ZrNb 2 O 8 (M=Ni, Mg, Co and Mn), ZnZr 0.8 Sn 0.2 Nb 2 O 8, Zn 0.9 Ti 0.8− x Sn x Nb 2.2 O 8 ( x =0‐0.15), ZnZrNbTaO 8, ZnTiNbTaO 8, (Mg 0.97 M 0.03 ) TiO 3 (M=Ni, Zn, Co and Mn), Ba(Co 0.2 Mg 0.8 ) 2 (VO 4 ) 2, Zn 3 Nb 2 O 8. These representative materials are pure and densified in the references.…”
Section: Resultsmentioning
confidence: 99%
“…The microwave dielectric properties of wolframite-type AZrB 2 O 8 (A = Mn, Zn, Mg, Co, Ni; B = Nb, Ta) and the structure-relationship were determined via combining the far-infrared and terahertz spectroscopy with P-V-L theory [87][88][89][90][91]. Partial replace of A-site (such as Mg 0.5 Zn 0.5 ZrNb 2 O 8 [92], Zn 1-x Co x ZrNb 2 O 8 [93][94][95]), Zr-site substitution of Zn(Ti 1-x Zr x )Ta 2 O 8 [96], ZnZr 1-x Sn x Nb 2 O 8 [97,98], doped Nb-site of MgZr(Nb 1-x Sb x ) 2 O 8 [99,100], ZnZrNbTaO 8 [101], MgZrNb 2-x (Sn 1/2 W 1/2 ) x O 8 [102], and nonstoichiometric MgZrNb 2+x O 8+2.5x [103] provided evidence that relative density, packing fraction, bond valence, and chemical bond characteristics majored the variation of microwave dielectric properties. To adjust the negative τ f values, the study about the relationship of TiO 2 on MgZrNb 2 O 8 [104] and ZnZrNb 2 O 8 [105] presented that co-exited ceramics would reach near zero τ f values.…”
Section: Rutile-trirutile/ixiolite/wolframite-columbite Type Ceramicsmentioning
confidence: 99%
“…3c and 3d) but the amount of precipitates could be estimated to be more than that of HR3C from the thickness of coarsened boundary size. Si is beneficial for the improvement of oxidation resistance in the steels but also increases the diffusion coefficient of alloy element [20]; hence, M 23 C 6 may have grown up by the diffusion of Cr in the 22Cr-25Ni-2.5Si steels. Figure 4 shows the isothermal oxidation mass change values of HR3C and 22Cr-25Ni-2.5Si austenitic stainless steels oxidized in air at 800°C.…”
Section: Microstructure Characterizationmentioning
confidence: 99%
“…3), a larger amount of M 23 C 6 was precipitated at the grain boundary as compared to the HR3C. Wang et al has reported that the M 23 C 6 carbides in the high-silicon 12% Cr ferritic/martensitic steels were oxidized during the exposure of in air, and playing a thirdelement effect for promoting the external oxidation of Si at lath boundaries [20]. Therefore, the M 23 C 6 of 22Cr-25Ni-2.5Si alloys may be helpful for the formation of SiO 2 oxides.…”
Section: Oxidation Behavior Of Samples Exposed At 800°cmentioning
confidence: 99%
See 1 more Smart Citation